POCT errors can lead to false potassium results - Buño Antonio; Oliver Paloma (Advances in Laboratory Medicine, 2021)
Point-of-care-testing (POCT) facilitates rapid availability of results that allows prompt clinical decision making. These results must be reliable and the whole process must not compromise its quality. Blood gas analyzers are one of the most used methods for POCT tests in Emergency Departments (ED) and in critical patients. Whole blood is the preferred sample, and we must be aware that hemolysis can occur. These devices cannot detect the presence of hemolysis in the sample, and because of the characteristics of the sample, we cannot visually detect it either. Hemolysis can alter the result of different parameters, including potassium with abnormal high results or masking low levels (hypokalemia) when reporting normal concentrations. Severe hyperkalemia is associated with the risk of potentially fatal cardiac arrhythmia and demands emergency clinical intervention. Hemolysis can be considered the most frequent cause of pseudohyperkalemia (spurious hyperkalemia) or pseudonormokalemia and can be accompanied by a wrong diagnosis and an ensuing inappropriate clinical decision making. A complete review of the potential causes of falsely elevated potassium concentrations in blood is presented in this article. POCT programs properly led and organized by the clinical laboratory can help to prevent errors and their impact on patient care.